Susu Kacang Merah Sebagai Substitusi Susu Sapi Dalam Es Kopi Susu Gula Aren - Fajri, Ilham; Wibawa, Idham Sakti (JURNAL GASTRONOMI INDONESIA, 2024)
Abstract Ready-to-drink (RTD) coffee is a drink that is quite popular among Indonesian people. Apart from its delicious taste, the price of ready-to-drink coffee is quite affordable for the public. RTD coffee is easy to find anywhere. This also pushed the sales volume of RTD coffee in Indonesia to reach 225 million liters this year. This amount increased by 3.2% compared to the previous year which was 218 million liters. Looking at the trend, the sales volume of ready-to-drink coffee continued to increase from 2015 to 2019. However, the figure dropped in 2020 due to the Covid-19 pandemic. Two years later, RTD coffee sales volume increased again. Sales of ready-to-drink coffee are expected to recover in 2023 to pre-pandemic levels. Euromonitor also stated that total coffee production in Indonesia will reach 11.35 million bags in 2022/2023. That number increased by 7% from 2021/2022 due to increased harvests in most of the main coffee producing regions. Many coffee lovers are allergic to cow's milk, this opens up opportunities for baristas to find or make alternative milk made from plant-based products.